Common complications of hemodialysis: A clinical review - Habas, Elmukhtar; Habas, Aml; Elgamal, Mohamed; Shraim, Bara; Moursi, Moaz; Ibrahim, Ayman; Danjuma, Mohamed; Elzouki, Abdel-Naser (Ibnosina Journal of Medicine and Biomedical Sciences, 2021)
Long-term hemodialysis (HD) is the main modality used in the treatment of end-stage renal disease (ESRD). It is associated with a variety of complications such as infection, amyloidosis, anemia, undernutrition, as well as musculoskeletal, and cardiovascular system (CVS) morbidities. CVS complications and HD-related infection are the main causes of death in ESRD patients on HD. Other complications such as stroke, disequilibrium syndrome occur during or post-HD. Missing dialysis sessions may lead to amongst others; death due to sudden cardiac arrhythmias; cardiac arrest due to electrolyte disturbance and/or severe overload. This review discusses the common complications of HD as well as recent advances that are likely to impact its outcome.
Keywords: Amyloidosis; cardiovascular disease; end-stage renal disease; hemodialysis; infection; long-term; renal osteodystrophy; undernutrition